Comparative microscopic examination of scales in 21 clupeid species from the Caspian Sea and the Indo-Pacific regions. (October 2020) - Purrafee Dizaj, Leyli; Esmaeili, Hamid Reza; Teimori, Azad; Abbasi, Keyvan
Highlights: The morphological analysis based on scale characteristics was largely consistent with the phylogenetic relationships of the studied clupeids. This study highlights that scale characters such as scale shape and size could be used as suitable features for the identification clupeids. Despite the general similarity of the scales, they may properly be used to estimate the phylogenetic relationships among clupeids. Abstract: The clupeid fishes are large filter-feeding organisms and have diverse groups of trophic guilds and habitats. They are known for their special body scale, which is unique among the other teleost fishes. Here, we examined microscopic characteristics of scales in 21 clupeid species from four marine resources, including the Caspian Sea, the Persian Gulf and the Gulf of Oman (Indian Ocean) and South China Sea (Haian Islands and Shanwei, Pacific Ocean) to evaluate if the scale features could properly contribute to understanding the taxonomic relationships in these fishes. Typically, the studied scales were morphologically categorized into two types; circular (i.e., true circular, cordate, discoidal) and pentagonal. Also, it was found that the number and the orientation of radii and continuous striae, the presence of pores at the posterior field, overall shape, striations on the posterior field, and scale sizes could be used as suitable features to classify the clupeids in species and genus levels. The result of morphological analysis based on the scale characteristics was largely consistent with the phylogenetic relationships of the studied species. This highlighted that morphological characteristics of the clupeid scale could adequately contribute to the understanding of taxonomic relationships in this large group.